(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This study evaluates the effect of incorporating of fly ash, waste glass powder or nano silica as a replacement for cement on the workability, compressive and flexural strength also rate of absorption (sorptivity) of concrete. The study followed the design of experiments (DoE) approach to test concrete mixes based on the response surface method (RSM). The experimental program included testing eight concrete mixes including reference mix with three investigated variables include fly ash, waste glass powder and nano silica at the replacement levels for cement of (30, 15 and 2) % respectively. The results show that the nano silica has a significant improvement of mechanical properties of concrete mixes, and the glass powder has a positive effect on the studied properties of the developed concrete mixes. While using fly ash presented less effect on the properties of studied concrete mixes. Besides, the target compressive strength at 28 days was achieved by incorporating fly ash, nano silica, waste of glass powder indicating the potential of using materials in the concrete mixes.